2015
DOI: 10.1007/s10014-015-0216-6
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A2 regulates angiogenesis and invasion phenotypes of malignant glioma

Abstract: BACKGROUND: Despite advances in multimodal therapy, patients with malignant glioma have a dismal prognosis. Aberrant angiogenesis and diffuse glioma cell invasion are major obstacles for effective treatment. Therefore, investigation of angiogenesis and invasion is essential for the development of a curative therapy. We established animal models that histologically mimic two invasive and angiogenic phenotypes of glioma, ie, angiogenesis-dependent invasion (J3T-1) and angiogenesis-independent invasion (J3T-2). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…VEGF-related drugs have been used in clinical applications [8]. Over the past several decades, work from several laboratories has shown that annexin A2 plays an important role in NV by interacting with VEGF [9, 10]. Furthermore, work on annexin A2/AX2R in regulation of NV has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…VEGF-related drugs have been used in clinical applications [8]. Over the past several decades, work from several laboratories has shown that annexin A2 plays an important role in NV by interacting with VEGF [9, 10]. Furthermore, work on annexin A2/AX2R in regulation of NV has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical and qRT-PCR studies showed high expression of AnxA2, VEGF and PDGF in glioblastoma cells. Moreover, staining intensity of VEGF and PDGF positively correlated with AnxA2 overexpression hence suggesting AnxA2 role in regulating angiogenesis (Onishi et al, 2015).…”
Section: Annexin A2 In Gbmmentioning
confidence: 96%
“…AnxA2 mediates glioma cell adhesion to endothelial cells and promotes production of angiogenic factors such as vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF) thus promotes neovascularization and invasion (Maule et al, 2016). In glioblastoma specimen, multiple satellites of tumour cells containing dilated blood vessels were found in brain parenchyma near brain tumour centre (Onishi et al, 2015). Immunohistochemical and qRT-PCR studies showed high expression of AnxA2, VEGF and PDGF in glioblastoma cells.…”
Section: Annexin A2 In Gbmmentioning
confidence: 99%
See 2 more Smart Citations